2020
DOI: 10.1101/2020.05.11.20098053
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parasites and their protection against COVID-19- Ecology or Immunology?

Abstract: Background: Despite the high infectivity of SARS-CoV-2, the incidence of COVID-19 in Africa has been slower than predicted. We aimed to investigate a possible association between parasitic infections and COVID-19. Results:Of the global 3.34 million COVID-19 cases and 238,628 deaths as at May 4 th 2020, Africa reported 0.029/3.3 million (0.88%) cases and 1,064/238,628 (0.45%) deaths. In 2018, Africa reported 213/229 million (93%) of all malaria cases, 204/229 million (89%) of schistosomiasis cases, and 271/1068… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 26 publications
(36 reference statements)
0
28
0
1
Order By: Relevance
“…Although SARS-CoV-2 is a new human pathogen, few studies have shown that conditions eliciting non-specific immune response such as BCG vaccination 37 38 and recurrent parasitic infections 39 may render some protection against COVID-19. Thus, widespread routine BCG vaccination and rampant parasitic infections in communities in Ethiopia and other African countries might have contributed to milder COVID-19 in such settings.…”
Section: Discussionmentioning
confidence: 99%
“…Although SARS-CoV-2 is a new human pathogen, few studies have shown that conditions eliciting non-specific immune response such as BCG vaccination 37 38 and recurrent parasitic infections 39 may render some protection against COVID-19. Thus, widespread routine BCG vaccination and rampant parasitic infections in communities in Ethiopia and other African countries might have contributed to milder COVID-19 in such settings.…”
Section: Discussionmentioning
confidence: 99%
“…One of them stipulates that helminths could worsen COVID-19 severity, due to their immunomodulatory effects involving type 2 immune response (52, 53). An alternative hypothesis is that pre-exposure to helminths infection could reduce the risk of severe COVID-19 outcomes, through a downregulation in the production of proinflammatory cytokines involved in the hyperinflammation of the lungs and ‘cytokine storm’ commonly observed in severe and fatal COVID-19 disease (18, 19).…”
Section: Discussionmentioning
confidence: 99%
“…We selected prevalence of malaria, soil-transmitted helminths, filariasis and schistosomiasis as indicators of prior exposure to endemic infections based on the literature (18,19,48,57) and on consultation with parasitology experts. Prior exposure to malaria was measured using age-standardised predicted parasite prevalence rate for children two to ten years of age for Plasmodium falciparum , and in all ages for Plasmodium vivax .…”
Section: Supplementary Filementioning
confidence: 99%
See 1 more Smart Citation
“…The immune profile of healthy Ethiopians shows evidence of chronic immune activation with significant low naïve cells but high activated memory cells, of both CD4+ and CD8+ T-cell subpopulations (Borkow et al, 2000;Hazenberg et al, 2000;Kassu et al, 2003;Tsegaye et al, 2003). Such immune characteristics in Ethiopians as compared to Europeans led us to the assumption that these could contribute to the phenomenon of milder COVID-19 symptomatology, as commonly found in SSA and elsewhere in the world (Chatterjee et al, 2020;Ssebambulidde et al, 2020). The postulation is that persistent immune activation due to continuous infections with parasites skews the immune system of populations in LMICs toward TH2 type and Treg immune responses that counteract the symptomatology associated with TH1 hyperinflammation.…”
Section: Impact Of Parasite-driven Microbiome Change On the Pathogenesis Of Covid-19mentioning
confidence: 97%